2008
DOI: 10.2310/6670.2008.00008
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Significant Carotid Artery Disease among a Cohort of 1,000 Egyptian Patients

Abstract: The objective of this study was to determine the prevalence of significant carotid artery disease (SCAD) in a cohort of Egyptian patients to compare it with matched groups of patients in published data of Western populations. One thousand consecutive patients referred for color flow duplex scanning of the carotid arteries were included. SCAD was defined as carotid stenosis > or = 50% or occlusion. There were 567 males (56.7%), and the mean age was 60.4 years. There were 382 (38.2%) patients presenting with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…This finding is in contrast with study results by Bishara et al [4] , which show that the prevalence of carotid artery disease in their cohort of 1,000 Egyptian patients was similar to that in matched patients of Western populations, and that significant stenosis was detected in 16% of symptomatic subjects.…”
contrasting
confidence: 56%
“…This finding is in contrast with study results by Bishara et al [4] , which show that the prevalence of carotid artery disease in their cohort of 1,000 Egyptian patients was similar to that in matched patients of Western populations, and that significant stenosis was detected in 16% of symptomatic subjects.…”
contrasting
confidence: 56%
“…82 One investigator reported that screening of asymptomatic patients is appropriate if they were aged $60 years and had three or more traditional atherosclerotic risk factors. 83 However, few direct comparative studies have evaluated the efficacy of screening with respect to the actual clinical outcomes of stroke or death. Most reported studies have used the prevalence of significant carotid stenosis in the studied populations as the actual outcome measure.…”
Section: Evidence and Rationalementioning
confidence: 99%